Konversi Modal Sosial Etis dalam Komunitas Bisnis Alumni Pesantren: Analisis Bonding, Bridging, dan Linking pada FORBIS IKPM Yogyakarta - Ridlo Zarkasyi, Muhammad; Cahyani, Meitria; Fithriana Wibisono, Vina (Indonesian Journal of Islamic Economics and Business, 2025)
This study examines the dynamics of social capital within an Islamic business community of pesantren alumni, using the Forum Bisnis (FORBIS) of the Ikatan Alumni Pondok Modern (IKPM) Yogyakarta as a case study. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and document analysis. The findings reveal that bonding social capital among FORBIS members is exceptionally strong, shaped by pesantren values such as brotherhood (ukhuwah), discipline, and internal trust. However, this bonding strength has not been effectively transformed into bridging or linking social capital. Key obstacles include psychological factors (feelings of hesitation and inferiority), cultural factors (conservative interpretations of adab), structural barriers (the absence of formal mechanisms for external relations), and the limited readiness of members’ businesses to enter formal networks. Consequently, social capital remains concentrated at the internal level and has not yet functioned as a strategic resource for expanding market access, partnerships, or institutional collaboration. This study highlights the need to strengthen organizational structures, develop business incubation programs, and establish linking mechanisms utilizing senior alumni networks to enhance the productive conversion of social capital within FORBIS and support the development of Islamic business ecosystems.